2017
DOI: 10.1016/j.bjorl.2016.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Rhinitis as an associated factor for anxiety and depression amongst adults

Abstract: AR and NAR are diseases associated to anxiety and depression, at least in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
1
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(35 citation statements)
references
References 24 publications
(32 reference statements)
0
31
1
2
Order By: Relevance
“…Forty studies were further excluded after full-text reading, leaving 24 primary studies included in the systematic review . Among the included papers, 13 studies solely reported results on depression (19,(21)(22)(23)(28)(29)(30)(31)(32)36,37,39,41) , one study solely reported results on anxiety (35) and 10 studies presented results on both depression and anxiety (18,20,(24)(25)(26)(27)33,34,38,40) . Of these 24 primary studies, 12 studies (20,(26)(27)(28)(29)(30)(34)(35)(36)38,39,41) presented OR from multivariable regression models and were included in our main analyses -11 studies (20,(26)(27)(28)(29)(30)34,36,38,39,41) provided results from multivariable models assessing the association between A...…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty studies were further excluded after full-text reading, leaving 24 primary studies included in the systematic review . Among the included papers, 13 studies solely reported results on depression (19,(21)(22)(23)(28)(29)(30)(31)(32)36,37,39,41) , one study solely reported results on anxiety (35) and 10 studies presented results on both depression and anxiety (18,20,(24)(25)(26)(27)33,34,38,40) . Of these 24 primary studies, 12 studies (20,(26)(27)(28)(29)(30)(34)(35)(36)38,39,41) presented OR from multivariable regression models and were included in our main analyses -11 studies (20,(26)(27)(28)(29)(30)34,36,38,39,41) provided results from multivariable models assessing the association between A...…”
Section: Discussionmentioning
confidence: 99%
“…Table 1 summarizes the characteristics of the 23 included primary studies assessing the association between AR and depression (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(36)(37)(38)(39)(40)(41) . These studies were published between 1991 and 2019 and their sample sizes ranged from 88 to 240 million participants, resulting in a total of more than 243 million participants.…”
Section: Studies Characteristicsmentioning
confidence: 99%
“…[110] Circulating cytokines can also lead to increased glucocorticoid output and receptor dysfunction under stressful situations[111], which has been shown to be associated with MDD [112]. Some cytokines (i.e., IL-1β, IL-2, frequently elevated in AR patients [113] can induce expression of the CNS enzyme indoleamine 2,3-dioxygenase [114], which induces production of kynurenine from tryptophan. The kynurenine: tryptophan ratio in turn is linked to depression and suicidal behavior through neurotoxic, glutamatergic and possibly serotonergic dysregulation in the CNS [115••117].…”
Section: Ar and Depressionmentioning
confidence: 99%
“…However, it can cause significant morbidity, through both the physical symptoms and its impact on quality of life and well-being [ 1 ]. It has a profound effect on many aspects of daily life such as sleep [ 2 ], work/school [ 3 ], and social life, having been shown to result in fatigue and mood changes [ 4 ], to impair cognitive function [ 5 ], and to lead to depression and anxiety [ 6 ].…”
Section: Introductionmentioning
confidence: 99%